Implementation of regional government information systems in the regional financial management study at the tolitoli regency environmental service - Edi Yanto; Sahwan Sahwan; Joko Prathomo (Institute of Computer Science (IOCS), 2023)
The era of digitalization affects the performance of an institution or organization, especially regional apparatus. It is necessary to apply regional government information systems to each existing regional device in order to provide convenience, smoothness, and optimization related to financial management. An integrated financial management system, through systems and networks as well as computerized technology, facilitates work units in existing regional apparatus so as to improve organizational performance and achievements. Through the implementation theory of Van Meter and Van Horn (1975), it is hoped that it can provide knowledge related to the implementation of local government information systems at the Tolitoli Environmental Service. Based on qualitative data analysis, it was found that: 1) Policy Standards and Targets have been running well, useful in setting and planning in accordance with the achievement of key performance indicators; 2) Operators are the key to the success of the system supported by the availability of facilities in the form of computerized devices and networks; 3) In terms of the characteristics of the implementing organization, the Environmental Service is an implementing element of the regional government in the environmental sector with the status of a mandatory affair that is not related to basic services; 4) Inter-organizational communication runs well and; 5) Disposition and Attitude of Executors in the form of knowledge and implementation of structured policies.